2017
DOI: 10.3389/fnins.2016.00614
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Changes in Response to Mechanical Pressure Stimulation of Skeletal Muscles Are Mediated by Cardiac Sympathetic Nerve Activity

Abstract: Stimulation of mechanoreceptors in skeletal muscles such as contraction and stretch elicits reflexive autonomic nervous system changes which impact cardiovascular control. There are pressure-sensitive mechanoreceptors in skeletal muscles. Mechanical pressure stimulation of skeletal muscles can induce reflex changes in heart rate (HR) and blood pressure, although the neural mechanisms underlying this effect are unclear. We examined the contribution of cardiac autonomic nerves to HR responses induced by mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This interpretation, however, remains tentative due to the small number of studies employing a sedation condition, differences in outcome measures employed and potentially confounding variables such as intervention design and the degree of pressure employed. Both sedation condition studies employed gentle massage techniques, whereas the majority of restricted sedation studies demonstrating stronger evidence for effects used greater pressure in the form of acupressure or reflexology, which may elicit more direct autonomic effects (Field, ; Watanabe & Hotta, ; Section ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation, however, remains tentative due to the small number of studies employing a sedation condition, differences in outcome measures employed and potentially confounding variables such as intervention design and the degree of pressure employed. Both sedation condition studies employed gentle massage techniques, whereas the majority of restricted sedation studies demonstrating stronger evidence for effects used greater pressure in the form of acupressure or reflexology, which may elicit more direct autonomic effects (Field, ; Watanabe & Hotta, ; Section ).…”
Section: Resultsmentioning
confidence: 99%
“…In the light of evidence that cortical processing may be a key mechanism underlying the benefits of gentle, medium‐velocity touch (Table , Figure b), gentle touch may have limited effectiveness for sedated patients due to reduced corticocortical and subcorticocortical connectivity (MacDonald, Naci, MacDonald, & Owen, ). In contrast, moderate pressure touch is suggested to elicit a relaxation response by increasing parasympathetic activity and/or reducing sympathetic activity (Field, ; Watanabe & Hotta, ). The mechanisms underlying the effects of moderate pressure touch may therefore be less reliant on cortical processes (Table ; Construction Principle 6).…”
Section: Resultsmentioning
confidence: 99%
“…Research has reported that static stretching increases heart rate and blood pressure [ 29 , 30 ]. Underlying mechanisms have been linked to muscle sympathetic nerve activity, cardiac sympathetic nerve activity, and vagal withdrawal [ 31 , 32 , 33 ]. In our study, sympathetic nervous activity increased during the resting phases after stretching, which deviates from some previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical pressure stimulation of skeletal muscles can induce reflex changes in HR and BP, although the neural mechanisms underlying this effect are unclear. 28 A recently published study showed that cardiac sympathetic nerve activity regulates HR responses to muscle mechanical pressure stimulation and that the direction of HR responses depends on the tonic level of the nerve activity, i.e., bradycardia occurs when the tonic activity is high, and tachycardia occurs when the activity is low. 28 On the other hand, we found no correlation between the VR and anthropometric measurements, which are more specific markers of obesity.…”
Section: Discussionmentioning
confidence: 99%